Arachniodes libingii sp. nov. and A. vietnamensis sp. nov. (Dryopteridaceae), two new ferns from southern China and central Vietnam - Lu, Ngan Thi; Nguyen, Linh Phuong; Le, Chi Toan; Nguyen, Thanh Trung; Zhang, Liang (Phytotaxa, 2021)
We here describe two new species Arachniodes libingii and A. vietnamensis (Dryopteridaceae) from southern China and central Vietnam, respectively. Our previous phylogenetic analysis found a close relationship between the two new species. Further morphological studies showed that the two species share short creeping rhizomes, blackish brown and lanceolate scales, papery laminae, aristate pinnules, dense scales along fronds, and entire indusia. However, A. libingii has deltoid-oblong laminae and apices abruptly acuminate-caudate, while A. vietnamensis has shortly ovate laminae and apices gradually acuminate.